Uterine Transplants – Considerations of Legal Frameworks, Access for Transgender Women, and Ethical Considerations - Santos Pinero, Dianelys Ire (Bioethica, 2025)
Uterine transplantations (UTx) are rapidly gaining popularity as an artificial reproductive technique (ART). Uterine transplantations (UTx) refer to a surgical procedure whereby a healthy uterus is transplanted from one person to another. Up to date, UTx procedures have been performed on cisgender women who struggle with some sort of infertility, whether that be Absolute Uterine Factor Infertility or Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome, a disorder where someone is born without a uterus. Though this procedure is not currently offered as routine treatment in any country worldwide, it is essential to determine the key ethical and legal debates surrounding the procedure in order to determine whether current organ transplantation laws are adequate for this procedure, or if new legislation is necessary in order to capture the complex nature of the procedure. UTX not only involves the routine complexities of any organ donations, such as kidney donations, but it also creates a unique level of added harm for both the donor and the recipient. Currently, no country has suggested to bring forward specific legislation regarding this procedure. However, I will argue that it is essential to view this ART as a different level of organ donation, thus requiring an individual set of legislation. UTx specific legislation will aid to combat inequalities and prevent coercion at an international level. This article will establish three main considerations regarding this procedure. Firstly, I will ask whether a new legal framework is required in order to deal with the issue of uterine transplants, or will it be sufficient to apply current rules regarding organ transplantations? I will analyse laws regarding access to UTx in the following countries: Sweden, Lebanon, the United Kingdom, and the United States., I will seek to establish the medical and ethical considerations regarding access to uterus transplants for transgender women, how it would be physiologically possible, and the importance of allowing access to uterus transplants for this subgroup of women. I will seek to point out a myriad of ethical issues that arise from the procedure, such as deceased donations, fair distribution, whether the procedure should be made available for cisgender and transgender men, the principle of harm and whether this level of harm to the donor and to the recipient could be ethically acceptable, and finally, the right to procreate and where UTx lies within this right. Ultimately, I will seek to establish that a new and innovative set of legislation should be implemented in order to encapsulate the complex nature of UTx.